Associations Between Acculturation and Oral Health Among Older Chinese Immigrants in the United States - Shaoqing Ge MPH; Bei Wu PhD; XinQi Dong MD, MPH (Gerontology and Geriatric Medicine, 2018)
Background: The aim of this study was to understand the associations between acculturation and oral health among older Chinese immigrants in the United States. Method: We used data from the PINE study, which included the foreign-born older Chinese immigrants ( N = 3,128). We measured acculturation by measuring participants’ length of stay and behavioral acculturation. Participants’ tooth and gum symptoms were the outcome variables. Results: Longer stay in the United States was significantly associated with fewer gum symptoms but not with tooth symptoms. Behavioral acculturation was not significantly associated with either tooth or gum symptoms. The middle tertile of behavioral acculturation, compared with its upper and lower tertiles, deemed to be a more significant risk factor of tooth/gum symptoms. In addition, older immigrants with more social interactions with the Americans were more likely to have tooth symptoms. Discussion: In the future, we will conduct a study using longitudinal data to help us better understand the relationship between acculturation and oral health in Chinese American population.